2019
DOI: 10.2196/13416
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based and Print-Delivered Computer-Tailored Physical Activity Intervention for Older Adults: Pretest-Posttest Intervention Study Comparing Delivery Mode Preference and Attrition

Abstract: Background Web-based interventions can play an important role in promoting physical activity (PA) behavior among older adults. Although the effectiveness of these interventions is promising, they are often characterized by low reach and high attrition, which considerably hampers their potential impact on public health. Objective The aim of this study was to identify the participant characteristics associated with the preference for a Web-based or a prin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 68 publications
0
25
1
Order By: Relevance
“…Previous studies have indicated that younger age [16][17][18][19], lower educational levels [20][21][22][23][24][25][26], and unemployment [24,27,28] are among the most reliable predictors of premature termination of studies or discontinuation of treatment compliance in several contexts. Psychological variables associated with poor compliance and retention include poor mental health [29][30][31][32][33][34] and low conscientiousness scores [35,36], and there is some evidence that high extraversion [37] and low agreeableness [1,38] might also be risk factors for dropout.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that younger age [16][17][18][19], lower educational levels [20][21][22][23][24][25][26], and unemployment [24,27,28] are among the most reliable predictors of premature termination of studies or discontinuation of treatment compliance in several contexts. Psychological variables associated with poor compliance and retention include poor mental health [29][30][31][32][33][34] and low conscientiousness scores [35,36], and there is some evidence that high extraversion [37] and low agreeableness [1,38] might also be risk factors for dropout.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous research has shown that preferences for intervention modality may vary by age, sex, BMI, or social or living environment [ 15 , 22 , 23 ]. Younger individuals seem to prefer eHealth to print-based interventions [ 22 , 23 ], whereas older or female individuals or those with an adverse weight status appear to be more likely to favor print-based interventions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous research has shown that preferences for intervention modality may vary by age, sex, BMI, or social or living environment [ 15 , 22 , 23 ]. Younger individuals seem to prefer eHealth to print-based interventions [ 22 , 23 ], whereas older or female individuals or those with an adverse weight status appear to be more likely to favor print-based interventions [ 22 ]. Unfortunately, in our study, we were not able to investigate variations by sociodemographic characteristics because only 7% of the sample changed groups at follow-up, and preference was not assessed at baseline, but only retrospectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations